Variability characterization of Bipolaris sorokiniana populations causing black point disease in wheat - MIRZA JAISH BEG; RAJIV K. SINGH, DINESH SINGH*, VARSHA TRIPATHI, (Indian Phytopathology, 2013)
Ten monoconidial isolates of Bipolaris sorokiniana from wheat seed of distant localities were tested for their variability. In pathogenic capabilities, the isolates differed strikingly irrespective of the host. The isolate from Sabour, Bihar was found to be most virulent followed by Kumarganj, UP; Hissar, Haryana and Ludhiana, Punjab. Colony characters of Kumarganj and Sabour isolates showed fastest growth, wavy with raised central zone, grayish black colour and irregular margin whereas Kalyani and Durgapura were slow growing isolates. Sporulation varied from fair to excellent with different isolates, but no definite relation was established. In conidiophore and conidial characters, the average length of conidiophore of Kumarganj isolate was maximum (143.32Î¼) as against the Dharwad, Karnataka isolate which had the minimum (132.52Î¼) average length. The average length of conidia of Kumarganj isolate was maximum (70.99Î¼) against the minimum (55.33Î¼) in Kalyani isolate. Maximum average width of conidia and conidiophore was associated with Sabour and Srinagar isolates, respectively. Regarding conidial germination percentage and its pattern, Sabour isolate resulted in the maximum (99%) germination with bipolar germination pattern followed by Kumarganj, Rewa, Ludhiana, Srinagar, Dharwad, Hissar, Mahabaleshwar, Kalyani and Durgapura isolates.